Effects of Residual Topramezone on Sprigged Hybrid Bermudagrass Establishment. Issue 1 (19th October 2017) - Begitschke, Erick; McCurdy, James; Philley, Wayne; Baldwin, Christian; Stewart, Barry; Richard, Michael; Kalmowitz, Kathie
Abstract : Topramezone is a broad‐spectrum selective herbicide currently labeled for postemergence weed control in turfgrass. Little is known about its residual effects on sprigged establishment of hybrid bermudagrass ( Cynodon dactylon L. Pers. × C. transvaalensis Burtt‐Davy). Research was conducted at the Mississippi State University Turfgrass Research Center on the R.R. Foil Plant Science Farm near Starkville, MS, during summer 2014 and 2015 to evaluate the effects of topramezone (0.049 kg a.i. ha −1 ) and prodiamine (0.84 kg ha −1 ) on hybrid bermudagrass (52 m3 ha −1 ) sprigged directly after herbicide application as well as 1, 2, and 4 wk after application (WAA). Percentage visual estimates of hybrid bermudagrass cover and normalized difference vegetative index (NDVI) were assessed 12 WAA. Visual cover was compared with nontreated plots sprigged on the same date. Regression estimates were calculated for visual hybrid bermudagrass cover and NDVI to demonstrate the effects of sprigging date after herbicide application. Topramezone did not reduce visual estimates of cover or NDVI when hybrid bermudagrass was sprigged directly after herbicide application in either year. Prodiamine did not reduce hybrid bermudagrass cover compared with the nontreated during 2014 but reduced hybrid bermudagrass cover at all sprigging dates except 1 WAA during 2015. Results suggest that topramezone is relatively safe to use for site preparation before sprigging hybrid bermudagrass at any time interval. Future research may assess topramezone in combination with other pre‐emergence herbicides for effective and economically viable alternatives to existing selective and nonselective herbicide applications within sprigged hybrid bermudagrass establishment.